Women in Sufism - Dominguez Diaz, Marta. (London ; New York)
xii, 192 sayfa
Keywords: “Exploring the diverse myriad of female religious identities that exist within the various branches of the Moroccan Sufi Order, Qādiriyya Būdshīshiyya, today, this book evidences a wide array of religious identities, from those more typical of Berber culture, to those characterised by a ‘sober’ approach to Sufism, as well as those that denote New Age eclecticism. The book researches the ways in which religious discourses are corporeally endorsed. After providing an overview of the Order historically and today, enunciating the processes by which this local tarīqa from North-eastern Morocco has become the international organization that it is now, the book explores the religious body in movement, in performance, and in relation to the social order. It analyses pilgrimage by assessing the annual visit that followers of Hamza Būdshīsh make to the central lodge of the Order in Madāgh; it explores bodily religious enactments in ritual performance, by discussing the central practices of Sufi ritual as manifested in the Būdshīshiyya, and delves attention into diverse understandings of faith healing and health issues. Women and Sufism provides a detailed insight into religious healing, sufi rituals and sufi pilgrimage, and is essential reading for those seeking to understand Islam in Morocco, or those with an interest in Anthropology and Middle East studies more generally“ -- Yayıncı.